2022
DOI: 10.1001/jamanetworkopen.2022.6722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bariatric Surgery on Risk of Complications After Total Knee Arthroplasty

Abstract: Key Points Question Does bariatric surgery reduce complication risk after total knee arthroplasty (TKA) in patients with severe obesity? Findings In this randomized clinical trial of 82 adults aged 65 years and younger with class II obesity, those who were scheduled to undergo TKA experienced fewer joint surgery complications after undergoing a bariatric procedure, compared with those who underwent TKA without weight loss intervention. Meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 41 publications
(84 reference statements)
1
35
0
Order By: Relevance
“…In a median follow-up of 2 years after TKA, 14.6% of patients in the MBS group incurred the primary outcome of composite complications, compared with 36.6% in the control (non-MBS) group (difference 22.0%, P = .02). Interestingly, TKA was declined by 29.3% of subjects in the MBS group because of symptom improvement following weight loss, compared with only 4.9% in the control group [ 73 ].…”
Section: Bridge To Other Treatmentmentioning
confidence: 99%
“…In a median follow-up of 2 years after TKA, 14.6% of patients in the MBS group incurred the primary outcome of composite complications, compared with 36.6% in the control (non-MBS) group (difference 22.0%, P = .02). Interestingly, TKA was declined by 29.3% of subjects in the MBS group because of symptom improvement following weight loss, compared with only 4.9% in the control group [ 73 ].…”
Section: Bridge To Other Treatmentmentioning
confidence: 99%
“…However, 2/41 patients did not have BS prior to their TKA, and 12/41 did not undergo any TKA in the intervention group, but were still included in the intention to treat analysis. Furthermore, the majority of the patient in the intervention group had undergone gastric banding which differ from the patients in our BS group [14].…”
Section: Discussionmentioning
confidence: 82%
“…Bariatric surgery (BS) has been shown to be the most effective method in achieving significant long-term weight loss for patients with obesity in comparison with nonsurgical interventions [ 25 ]. A recent randomized control trial, analyzing the weight change after TKA in patients with prior BS or not, demonstrated that 12 of the 41 patients who had received BS did no longer require a TKA since their symptoms had improved [ 26 ]. The question arises if we should routinely recommend patients with obesity that fail to lose weight through other methods, the possibility to perform BS prior to their knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%